Case report: Autonomic and endocrine response in the process of brain death in a child with hypoxic-ischemic brain injury - Hayashi, Kenichiro; Uchida, Kaname; Ota, Hidehito; Tanaka, Hiroyuki; Maezawa, Mieko; Matsui, Hikoro (Frontiers in Pediatrics, 2022)
Background: The causes of brain death include cerebral herniation and brainstem ischemia. Neuroendocrine failure or a series of autonomic nervous system disorders are clinically recognized in the transition to brain death among patients with critical brain injuries. An accurate evaluation of these physiologic instabilities and biomarkers is essential to assess the severity and prognosis of pediatric brain injury as well as to initiate supportive care. This case report presents a detailed evaluation of the autonomic nervous system and endocrine function during the transition to brain death in infantile hypoxic-ischemic brain injury by analyzing the heart rate variability and endocrine status. Case Presentation: A one-year-old previously healthy boy went into cardiac arrest after choking on a toy at home. Although spontaneous circulation returned 60 minutes after cardiopulmonary resuscitation, no cerebral activity or brainstem reflexes were observed after 18 hospital days. The heart rate variability was assessed by analyzing the generic electrocardiogram data. Rapid spikes or drops in the total power of the heart rate variability, accompanied by a cortisol surge, as well as an alternating surge of high- and low-frequency domain variables were detected in the process of brain death. Conclusion: The heart rate variability assessment combined with endocine provides a better understanding of the clinical course of patients undergoing brain death. It accurately detects the loss of brain stem function, which allows physicians to provide the appropriate supportive care.